Kepatuhan Penggunaan Masker Pada Pedagang Lapak Sayur Sebagai Upaya Pencegahan Penyakit Covid-19 di Pasar Beringharjo Yogyakarta - Sri Yuni Tursilowati; Silviana Utami; Syamsinar Syamsinar (STIKes Surya Global Yogyakarta, 2022)
ABSTRACT Background of Study : COVID-19 is an infectious disease caused by the newly discovered corona virus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and has been declared a world pandemic by WHO (WHO, 2020) since March 11, 2020 The spread of the COVID-19 outbreak is very fast and deadly, the transmission is transmitted through physical contact, mouth, eyes, and nose. Based on the results of the preliminary study, it is known that the compliance with the use of masks by traders at Beringharjo Market is still low, from 10 traders seen 3 people who do not wear masks and 5 people who wear masks when serving buyers after pinning them on their chins, and 2 people using masks.Methods : This type of research is quantitative with a cross sectional design. The research population was 93 vegetable stall traders at Beringharjo Market. Sampling using Total Sampling. Results : Knowledge is significantly related to compliance with the use of masks with Chi Square test results showing a significant value of P Value of (0.002) (0.05), there is a correlation between attitude and adherence to the use of masks based on Chi Square test obtained a significant value of P Value of (0.007 ) (0.05) and there is a correlation between supervision and compliance with the use of masks, but compliance with the use of masks is not related to gender.Conclusion : There is a correlation between knowledge, attitude, supervision and compliance with the use of masks, while the gender of traders is not significantly related to compliance with the use of masks Keywords: Knowledge, Attitude, Supervision, Compliance, Masks, COVID-19